1984
DOI: 10.1161/01.cir.69.5.991
|View full text |Cite
|
Sign up to set email alerts
|

Rethrombosis after reperfusion with streptokinase: importance of geometry of residual lesions.

Abstract: We tested the hypothesis that lesion rethrombosis after streptokinase reperfusion is related to luminal size of the residual stenosis. Two independent techniques of analyzing coronary angiograms, quantitative coronary angiography and computer-based videodensitometry, were used to estimate the size of the residual lumen immediately after discontinuation of streptokinase. These techniques were selected because they provide independent estimates of cross-sectional area of a lesion with high degrees of reproducibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 326 publications
(46 citation statements)
references
References 31 publications
1
45
0
Order By: Relevance
“…[1][2][3][4] Even in patients who reperfuse initially the clinical outcome is often complicated by a residual high-grade stenosis56 and by early reocclusion.7 8 Evidence from studies in experimental animal preparations suggest that this may in part be due to platelet activation since interventions that inhibit platelet function enhance the thrombolytic response to streptokinase9 and prevent reocclusion. 10 Whether platelet activation also plays a role in modulating the response to streptokinase in patients with acute myocardial infarction is unknown.…”
mentioning
confidence: 99%
“…[1][2][3][4] Even in patients who reperfuse initially the clinical outcome is often complicated by a residual high-grade stenosis56 and by early reocclusion.7 8 Evidence from studies in experimental animal preparations suggest that this may in part be due to platelet activation since interventions that inhibit platelet function enhance the thrombolytic response to streptokinase9 and prevent reocclusion. 10 Whether platelet activation also plays a role in modulating the response to streptokinase in patients with acute myocardial infarction is unknown.…”
mentioning
confidence: 99%
“…The minimum cross-sectional area of the totally occluded lesion in patients with acute infarction usually inc reases in the first 10 days after thrombolysis, suggesting that further dissolution of thrombus occurs with time. 15 Figure 6 illustrates how thrombus can reside in and disguise plaque disruption. In this angiogram obtained from a patient with acute infarction (before thrombolysis), the thrombus appears to be attached to the coronary wall (right anterior oblique 45 degree view), but plaque ulceration is not evident.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of residual coronary stenosis after reperfusion appears to be the best single predictor. Harrison et al (1984) used quantitative angiography to carefully determine the degree of stenosis following streptokinase. They found that all 7 patients with reocclusion had residual stenoses greater than 90% of the coronary diameter.…”
Section: Introductionmentioning
confidence: 99%